What is the difference between a moral realist and a moral anti-realist? - Clark, W; William Clark (2013)
This paper addresses the question of how to distinguish moral realism from moral anti-realism. An influential view, prevalent primarily due to the work of Michael Dummett, appeals to semantic features of realism such as truth, bivalence, and surface form. However, minimalist accounts enable an anti-realist to appropriate any such semantic feature. The semantic characterisation is thus unable to distinguish adequately between moral realists and moral anti-realists. This is the problem of Creeping Minimalism. An alternative characterisation of the debate is proposed, making use of the distinctively metaphysical criteria of ontological inclusion/exclusion. Semantic minimalism is not an issue here, and the possibility of minimalism about ontology is shown to be incompatible with both realism and anti-realism, thus preventing the recurrence of Creeping Minimalism.